2001
DOI: 10.1159/000047253
|View full text |Cite
|
Sign up to set email alerts
|

Lateralization of Minicolumns in Human Planum temporale Is Absent in Nonhuman Primate Cortex

Abstract: Gross analyses of large brain areas, as in MRI studies of macroanatomical structures, average subtle alterations in small regions, inadvertently missing significant anomalies. We developed a computerized imaging program to microscopically examine minicolumns and used it to study Nissl-stained slides of normal human, chimpanzee, and rhesus monkey brains in a region of the planum temporale. With this method, we measured the width of cell columns, the peripheral neuropil space, the spacing density of neurons with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
109
1
2

Year Published

2002
2002
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(118 citation statements)
references
References 74 publications
6
109
1
2
Order By: Relevance
“…Also, Urbanc et al (25) used a crosscorrelation density-map method to study spatial relationships between the position and morphology of plaques with changes in neuronal architecture and revealed a focal neuronal toxicity associated with thioflavin S-positive plaque deposits in both AD and transgenic mice. Others, such as Casanova and Buxhoeveden, developed a method to quantify individually identified microcolumns, applying it to different human brain disorders (e.g., autism) (9)(10)(11)27), ʈ and to identify microcolumnar organization across species (28)(29). ** Their method requires that sections be oriented so that visually observed microcolumns align vertically.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Urbanc et al (25) used a crosscorrelation density-map method to study spatial relationships between the position and morphology of plaques with changes in neuronal architecture and revealed a focal neuronal toxicity associated with thioflavin S-positive plaque deposits in both AD and transgenic mice. Others, such as Casanova and Buxhoeveden, developed a method to quantify individually identified microcolumns, applying it to different human brain disorders (e.g., autism) (9)(10)(11)27), ʈ and to identify microcolumnar organization across species (28)(29). ** Their method requires that sections be oriented so that visually observed microcolumns align vertically.…”
Section: Discussionmentioning
confidence: 99%
“…These differences suggest that alterations in minicolumn organization-in autism-may have a profound impact on hemispheric specialization and functions that dependent on hemispheric specialization (such as language). In normal brain, the width of minicolumns and the distance between the columns is larger on the left than on the right [Seldon, 1981a[Seldon, , 1981b[Seldon, , 1982Buxhoeveden et al, 2001]. Seldon [1981aSeldon [ , 1981bSeldon [ , 1982 also showed that pyramidal cells in the posterior language cortex on the left contacted fewer columnar units than on the right.…”
Section: Brain Serotonin In Autistic Childrenmentioning
confidence: 97%
“…This implies that unique aspects of human language may result from derived changes in one or more of these regions, along with, perhaps, changes in how they interface with each other during development and language processing. One example may be the planum temporale, a region associated with language processing that appears to have undergone internal changes in the organization of minicolumns compared with chimpanzees, and specifically in the left hemisphere (85). Some regions involved in human language processing exhibit substantial laterality (83), have greater connectivity between them via white matter pathways (86), and have greater connectivity to other brain areas than do orthologous regions in nonhuman primates (87).…”
Section: Explaining Human Cognitionmentioning
confidence: 99%